PENGARUH SISTEM PENGENDALIAN INTERNAL PEMERINTAH TERHADAP PENCEGAHAN FRAUD PADA PEMERINTAH DAERAH KOTA PALU - Astriyani, Nini (Katalogis, 2017)
The purpose of this research is to know and analyzed: 1). The influence of government internal controlling system to prevent fraud in Government of Palu City. 2). The influence of controlling environment to prevent fraud in government of Palu city. 3) The influence of risk assessment to prevent fraud in government of Palu city. 4) The influence of controlling activity to prevent fraud in government of Palu city. 5) the influence of information and communication to prevent fraud in government of Palu City. 6) The influence of monitoring to prevent fraud in government of Palu city, the statistical test used multiple regression analysis with SPSS 16.0 program shows that: 1) The government internal controlling system with the same effect and significant impact in prevention fraud in government of Palu City. 2) Controlling environment has no significant effect on the prevention of fraud in government of Palu city. 3). Risk assessment has significant effect on prevention fraud in government of Palu city. 4). Controlling activity has no significant impact in prevent fraud in government of Palu city. 5) Information and communication has no significant effect on prevent fraud in government of Palu city. 6) monitoring has significant effect to prevent fraud in government of Palu city.